ChemInform Abstract: A New Type of KYP2O7 Synthesized by the Boric Acid Flux Method and Its Luminescence Properties. Issue 6 (21st January 2016) - Jiang, Yu; Liu, Wei; Cao, Xiyu; Su, Ge; Cao, Lixin; Gao, Rongjie
Abstract: Single crystals of a new phase of KYP2 O7, r‐KYP2 O7, are prepared by a low‐temperature H3 BO3 flux method using a 1:1:8 molar mixture of YF3, H3 BO3, and KH2 PO4 (autoclave, 573 K, 3 d; cooling to 453 K at a rate of 1 K/h).